The Timing of Vision – How Neural Processing Links to Different Temporal Dynamics - Masquelier, Timothée; Albantakis, Larissa; Deco, Gustavo (Frontiers in Psychology, 2011)
We review here our recent attempts to model the neural correlates of visual perception with biologically-inspired networks of spiking neurons, emphasizing the dynamical aspects. Experimental evidence suggests distinct processing modes depending on the type of task the visual system is engaged in. A first mode deals with rapidly extracting the glimpse of a visual scene in the first 100ms after its presentation. The promptness of this process points to mainly feedforward processing, which may be shaped by Spike Timing-Dependent Plasticity. Our simulations confirm the plausibility and efficiency of such a scheme. A second mode can be engaged whenever one needs to perform finer perceptual discrimination through evidence accumulation. Here, our simulations, together with theoretical considerations, show how predominantly local recurrent connections and long neural time-constants enable the integration and build-up of firing rates on this timescale. A third mode, involving additional top-down attentional signals, is relevant for more complex visual scene processing. In the model, as in the brain, these top-down attentional signals shape visual processing by biasing the competition between different neuron pools. The winning pools may not only have a higher firing rate, but also more synchronous oscillatory activity. This fourth mode, oscillatory activity, leads to faster reaction times and enhanced information transfers in the model. This has indeed been observed experimentally. Moreover, oscillatory activity can encode information in the spike phases with respect to the oscillatory cycle. This phenomenon is referred to as “Phase-of-Firing Coding”, and experimental evidence for it is accumulating in the visual system. Simulations show that this code can again be efficiently decoded by STDP. Future work should focus on continuous natural vision, bio-inspired hardware vision systems, and novel experimental paradigms to further distinguish current modeling approaches.